Forming Character With Morals Prophet Muhammad Saw - Imam Tabroni; Dean Dwi Putra; Najah Adawiah; Rosmiati (East Asian Journal of Multidisciplinary Research, 2022)
Character education can be characterized by a whole-souled, wholesome, moral, and disposition education at rendering good decisions, maintaining what is good, and wholeheartedly displaying goodness in daily life. The prophet (peace and blessings be upon him) was the messenger of god and the educator. He got disciplined directly from his Lord so as to have the most perfect character on the face of this earth, so as to become a great man with the testimony of god enshrined in his word: “and how virtuous you truly are” the great testimony of god of the prophet (peace) is evidence that his moral character is great and glorious since the creation of it. He was renowned among his kind as honest and trustworthy. As a majestic being, he had the glorious duty of the supreme being, the edifying and perfecting of men, as the prophecy says: “that I was sent forth to perfect men.” He succeeded in carrying out a great commission by turning the evil community into a society of faith and civility, while printing out noble characters.